2020
DOI: 10.1590/1984-70332020v20n1a10
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield, anthesis-silking interval and drought tolerance indices of tropical maize hybrids

Abstract: Water deficit stress is the abiotic factor with the highest impact on crop yield. The objective of this study was to evaluate grain yield (GY), the anthesis-silking interval (ASI) and drought tolerance indices in maize hybrids. We evaluated GY and the ASI of 86 hybrids under two moisture levels (normal irrigation and water stress) for three consecutive years. The stress susceptibility index, water stress tolerance, drought resistance coefficient, drought resistance index, stress tolerance index and harmonic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Moreover, inheritance of good plant height (relatively taller plants) in hybrids indicates an advantage of producing enough assimilates for partitioning into sinks (grains), which could contribute to high GY. The high R estimate observed for ASI under low soil moisture environments confirmed the results of other researchers (Bänziger et al, 2000;Magorokosho & Tongoona, 2003;Santos et al, 2020), who determined that ASI is a predictable secondary trait for identifying drought-tolerant maize genotypes. It was striking to find higher R estimates for most traits under optimal growing conditions relative to their counterparts under drought.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, inheritance of good plant height (relatively taller plants) in hybrids indicates an advantage of producing enough assimilates for partitioning into sinks (grains), which could contribute to high GY. The high R estimate observed for ASI under low soil moisture environments confirmed the results of other researchers (Bänziger et al, 2000;Magorokosho & Tongoona, 2003;Santos et al, 2020), who determined that ASI is a predictable secondary trait for identifying drought-tolerant maize genotypes. It was striking to find higher R estimates for most traits under optimal growing conditions relative to their counterparts under drought.…”
Section: Discussionsupporting
confidence: 86%
“…The results implied that, for this set of inbred lines, ASI and plant height are stable traits that could be transferred to hybrids even under limited soil moisture conditions. Hybrids with low and stable ASI under drought would consistently have fewer days between anthesis and silking under drought for (Bänziger et al, 2000;Magorokosho & Tongoona, 2003;Santos et al, 2020), who determined that ASI is a predictable secondary trait for identifying drought-tolerant maize genotypes. It was striking to find higher R estimates for most traits under optimal growing conditions relative to their counterparts under drought.…”
Section: Discussionmentioning
confidence: 99%
“…In maize, silk (female) developmental events have been overlooked because of the complexity involved in phenotyping or due to the acropetal development of silk and the short duration of its life span (McNinch et al, 2020). Despite the challenges of phenotyping, silk development in maize was to be the key factor affecting pollination and yield determination (Borrás et al, 2007; Nielsen, 2020; Santos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among the traits, ASI differed significantly between the best and worst performing hybrids and mid‐parents grown under HMDS, while no significant differences were observed under WW conditions. Several studies on abiotic stress tolerance reported the usefulness of ASI as good indicator for stress tolerance (Bolaños & Edmeades, 1996; Ribaut et al, 1996; Santos et al, 2020). The highest yielding hybrids were taller than the poorest yielders under both HMDS and WW conditions, and this implies that selection of taller plants could improve GY.…”
Section: Discussionmentioning
confidence: 99%